EFEKTIVITAS PSAK 69 DALAM PENGELOLAAN ASET BIOLOGIS DI PERUSAHAAN PERKEBUNAN - Serly Novianti; Aljufri Aljufri; Zaharman Zaharman (Komunitas Manajemen Kompetitif, 2026)
The Financial Accounting Standard Statement (PSAK) 69 on Agriculture is implemented in Indonesia to increase the transparency and relevance of biological asset reporting through fair value, less cost to sell-based measurements. This study aims to analyze the effectiveness of the implementation of PSAK 69 in the management of biological assets in plantation companies in Indonesia in 2024. The research method used is a qualitative descriptive approach with analysis of annual financial statements and accounting disclosures from five plantation companies The results of the study show that all sample companies have implemented PSAK 69 in the presentation of biological assets, but the effectiveness still varies. From the recognition aspect, the entire company has separated biological assets from fixed assets. In terms of measurement, 80% of companies use fair value, but most have not fully disclosed their assumptions and valuation methods in detail. Inconsistent disclosures led to differences in asset valuations and fluctuations in net income between periods. The implementation of PSAK 69 is considered effective in increasing the relevance and comparability of financial statements, but it has not been optimal in terms of assessment transparency and consistency of disclosure. This study concludes that the effectiveness of PSAK 69 in the plantation sector in Indonesia has been formally achieved but still requires substantive improvement, especially in the aspects of determining fair value, human resource competence, and audit supervision. The results of the research are expected to be input for plantation companies, regulators, and academics to strengthen the implementation of fair value-based accounting in the agricultural sector